Improvement of the Bag-Mediated Filtration System for Sampling Wastewater and Wastewater-Impacted Waters - Fagnant, Christine Susan (Food Environ Virol, 2017)
Environmental surveillance of poliovirus (PV) plays an important role in the global program for eradication of wild PV. The bag-mediated filtration system (BMFS) was first developed in 2014 and enhances PV surveillance when compared to the two-phase grab method currently recommended by the World Health Organization (WHO). In this study, the BMFS design was improved and tested for its usability in wastewater and wastewater-impacted surface waters in Nairobi, Kenya. Modifications made to the BMFS included the size, color, and shape of the collection bags, the filter housing used, and the device used to elute the samples from the filters. The modified BMFS concentrated 3–10 L down to 10 mL, which resulted in an effective volume assayed (900–3000 mL) that was 6–20 times greater than the effective volume assayed for samples processed by the WHO algorithm (150 mL). The system developed allows for sampling and in-field virus concentration, followed by transportation of the filter for further analysis with simpler logistics than the current methods. This may ultimately reduce the likelihood of false-negative samples by increasing the effective volume assayed compared to samples processed by the WHO algorithm, making the BMFS a valuable sampling system for wastewater and wastewater-impacted surface waters.